Disclosure of medical errors to patients by medical professionals: a protocol for a qualitative systematic review - Guiru Chen; Rongrong Huang; Henyu Xiong (BMJ Open)
Introduction Although the disclosure of medical errors is an integral component of medical ethics, it remains inconsistent in practice worldwide. Despite various explanations of why healthcare professionals reveal their mistakes to patients, comprehensive comparisons and evaluations of this topic remain lacking. The objective of this review is to evaluate the experience of medical error disclosure among medical professionals who have been involved in such errors.Methods and analysis This work will focus on studies involving medical professionals from various countries who work in hospital settings and have obtained an understanding of and firsthand experience with medical error disclosure. This review will include qualitative studies. Studies published in databases such as PubMed, Embase, EBSCO, OVID, Web of Science, ScienceDirect, China National Knowledge Infrastructure, Wanfang Data and Cochrane Library from 1 January 2000 to 30 April 2024 will be searched as part of this research. Additionally, OpenGrey will be searched manually to obtain supplementary information. The search will be conducted starting in May 2024 and will include both Chinese-language and English-language literature. The systematic review will follow the Joanna Briggs Institute’s (JBI) methodology for systematic reviews of qualitative evidence and use the JBI System for the Unified Management, Assessment and Review of Information online program. Study authenticity will be investigated via the Qualitative Research Authenticity Evaluation Tool provided by the JBI Evidence-Based Health Care Centre, and data extraction will be performed via the Qualitative Assessment and Review Instrument data extraction tool. The results will be integrated via a pooled integration methodology and evaluated in terms of reliability via the ConQual qualitative systematic evaluation evidence grading tool.Ethics and dissemination Ethical approval is not required for the study because the review will be based on pre-existing data available in the literature. The results of this systematic review will be submitted to peer-reviewed journals and presented at relevant conferences.PROSPERO registration number CRD42024494360.